Association of TNIP1 polymorphisms with hepatocellular carcinoma in a Northwest Chinese Han population. Issue 12 (26th March 2021) - Shi, Yuting; Zhang, Lihua; Bao, Yang; Wu, Pengfei; Zhang, Xiaoli
Abstract : Abstract: Study has demonstrated that TNIP1 polymorphisms are associated with an increased risk of HBV-induced hepatocellular carcinoma (HCC). The purpose of this study was to investigate the correlation between polymorphisms in TNIP1 and HCC risk in a Northwest Chinese Han population. A case–control study was conducted including 473 Hepatocellular carcinoma patients and 564 healthy controls. Three SNPs (rs3792792, rs7708392, and rs10036748) were genotyped with Sequenom MassARRAY technology and their associations with HCC risk were analyzed. These data were evaluated using the Chi-square test/Fisher's exact test, genetic model analysis, and haplotype analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the association. Patients with the "G" allele of TNIP1 rs7708392 showed a significantly increased risk of HCC (OR = 1.24, 95%CI: 1.01–1.52, P = .042). Significant association was also shown between TNIP1 rs7708392 and HCC susceptibility in Additive model (OR = 1.25; 95% CI = 1.01–1.54; P = .040). Besides, we also found that the "GC" haplotype of rs7708392 and rs10036748 was significantly associated with higher occurrence of HCC (OR = 1.25, 95% CI: 1.01–1.54, P = .039). These results demonstrate that TNIP1 polymorphisms are associated with increased HCC risk in a Northwest Chinese Han population for the first time, which warrants further investigation in the future.